Modelling thermal fluxes at the soil surface. Issue 6 (19th October 2016) - Muñoz-Criollo, José Javier; Cleall, Peter John; Rees, Stephen William
Abstract : This paper investigates the impact that various representations of thermal fluxes at the soil surface have on the estimation of seasonal variations in temperature and stored thermal energy in the soil close to the surface. Three theoretical formulations representing turbulent, non-turbulent and vegetation-covered soil surface conditions are considered. The influence of shading from nearby objects (e.g. vegetation) has also been investigated. Numerical predictions of soil temperature and stored thermal energy are compared with experimental results from a large-scale field test (performed by others). The results of both one-dimensional and two-dimensional simulations are shown to be capable of representing specific aspects of field behaviour. Various sources of meteorological data have been used to define surface boundary conditions. In particular, simulations were performed using ( a ) data measured on-site, ( b ) data obtained from the British Atmospheric Data Centre and ( c ) data generated using analytical expressions from the literature. It was found that correct representation of the heat transfer processes occurring at the soil surface is of critical importance. In particular, it was found that the use of publicly available sources of data, or mathematical/analytical expressions for meteorological data, may be adequate when on-site measurements are not available.